1976
DOI: 10.1111/j.1365-2141.1976.tb01881.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Binding of Folates by Body Fluids

Abstract: It is useful to differentiate between saturated folate binders in serum (carrying endogenous folate) and unsaturated binders (investigated in the present study). These two groups of binders need not necessarily be chemically identical and the unsaturated binder may even be an in vitro artifact, especially when measured with non-physiological folates. Macromolecular binding of radio-active N-5-methyl tetrahydrofolic acid (CH3H4PteGlu) and/or folic acid (PteGlu) by human serum and urine was assessed by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Evidence exists that this binder may withhold folate from living cells [5,18], but its true functional significance remains obscure. It is present in normal plasma or serum in minor quantities only, rarely rising above 1 /¿g/1 [5][6][7]12]. It has been suggested that the unsaturaled binder is structurally similar to the saturat ed binder of endogenous folate [9,15,16,24],…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence exists that this binder may withhold folate from living cells [5,18], but its true functional significance remains obscure. It is present in normal plasma or serum in minor quantities only, rarely rising above 1 /¿g/1 [5][6][7]12]. It has been suggested that the unsaturaled binder is structurally similar to the saturat ed binder of endogenous folate [9,15,16,24],…”
Section: Discussionmentioning
confidence: 99%
“…The unsaturated folate-binding capacity of plasma was measured after incuba tion with excess " C-5CH3H4PteGlu and 3H-PteGlu added simultaneously as pre viously described [12], except that free radiofolate was removed by dialysis and not by charcoal adsorption.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations